Sports buildings - Konya, Allan (London, United Kingdom : Architectural Press, 1986)
This book main purpose is to provide all those involved in the initial stages of the building process - clients, users, and members of the design team - with a set of tools.
Section 1: General -- Introduction -- Inception and the preliminary brief -- Section 2: Sports and recreation buildings -- Introduction -- Inception and initial brief -- Feasibility -- Detailed brief -- Outline proposals/scheme design -- Appendices.
Includes bibliographical references.
Keywords: SPORTS FACILITIES -- DESIGN AND CONSTRUCTION